2022
DOI: 10.1017/s0954579422000682
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional spillover between maladaptive parenting and peer victimization and the mediating roles of internalizing and externalizing problems: A within-person analysis among Chinese early adolescents

Abstract: Parenting practices and relationships with peers are crucial aspects of youth socialization. Although theoretically expected reciprocal associations between changes in maladaptive parenting and adolescent peer victimization exist, there is a lack of studies that examine this link and address the mediating mechanisms at the within-person level. This longitudinal study examined reciprocal relations between peer victimization and two types of maladaptive parenting including harsh punishment and psychological cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In addition, on the premise that social capital such as popularity and friendship among peers is a powerful weapon against victimization, adolescents with internalizing problems are in unfavorable situations because they are more likely to have difficulties building up their interpersonal network. In the study on peer victimization and its relationship to parenting style, Zhou and colleagues discovered the mediation role of internalizing difficulties, which significantly predicts the likelihood of peer abuse at a within-person level [19]. Another study also confirmed the results, suggesting that adolescents with internalizing problems tend to be viewed as less amiable and socially incompetent among peer groups and accordingly be treated as weak targets by aggressors [4].…”
Section: Internalization Problemsmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, on the premise that social capital such as popularity and friendship among peers is a powerful weapon against victimization, adolescents with internalizing problems are in unfavorable situations because they are more likely to have difficulties building up their interpersonal network. In the study on peer victimization and its relationship to parenting style, Zhou and colleagues discovered the mediation role of internalizing difficulties, which significantly predicts the likelihood of peer abuse at a within-person level [19]. Another study also confirmed the results, suggesting that adolescents with internalizing problems tend to be viewed as less amiable and socially incompetent among peer groups and accordingly be treated as weak targets by aggressors [4].…”
Section: Internalization Problemsmentioning
confidence: 86%
“…Parental style significantly shapes children's traits and behaviors, for example, self-competence, extrovert versus introvert personality, and social skills which are closely related to the interpersonal connection. There is a bidirectional prediction between parental psychological control and peer victimization [19]. As explained by self-determination theory, psychological control stifles adolescents' ability of autonomy, and satisfaction with relationships, leading to psycho-social malfunctioning [22].…”
Section: Parental Psychological Controlmentioning
confidence: 99%